THE ROLE OF THE JOMBANG DISTRICT SOCIAL SERVICE IN SOCIAL PROTECTION AND CAPACITY DEVELOPMENT FOR PERSONS WITH DISABILITIES IN JOMBANG REGENCY - Temi Puji Lestari; Ertien Rining Nawangsari (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
Currently, there are still many people with disabilities who face various problems in welfare. Likewise in Jombang Regency there are still many people with disabilities who experience welfare problems. Seeing the problems faced by people with disabilities, the central government and local governments both provincial and district/city continue to pay attention to people with disabilities to overcome their welfare problems. Jombang District Social Service in an effort to overcome social welfare , persons with disabilities have the duty and function to provide social protection and capacity building for persons with disabilities . The purpose of this research is to find out The Role of the Social Service of Jombang Regency in Social Protection and Capacity Development for Persons with Disabilities in Jombang Regency. The type of research used in this research is descriptive qualitative. The data sources used in this research are primary data and secondary data . Data collection techniques used in this study , namely observation , interviews , and documentation related to information in the field. The results showed that the Social Service of Jombang Regency had carried out its role in providing Social Protection and Capacity Development for Persons with Disabilities in Jombang Regency. Based on the results of field analysis, the role of the Jombang District Social Service refers to the theory of Gede Diva (Putra, 2015) , which states that an effective and optimal government role includes the role of facilitator, regulator, and catalyst, which is adjusted to Jombang Regent Regulation Number 49 of 2018 Regarding the Position, Organizational Structure, Main Duties and Functions and Work Procedures of the Jombang Regency Social Service.